Mammary neoplasia in common brushtail possums: case report and retrospective identification of additional cases. Issue 6 (24th February 2020) - Setyo, L; Donahoe, SL; Rose, K; Spielman, D
Abstract : Background: Mammary neoplasia in possums have been sporadically reported in the literature. Case report: An adult common brushtail possum with severe dyspnoea warranting euthanasia was submitted for postmortem examination. Necropsy revealed a firm pale tan multilobulated mammary mass which contained pale tan tissue on section. Mammary carcinoma with metastases to the lungs, pleura, intercostal muscles and reproductive tract was diagnosed microscopically. Spontaneous neoplasms in possums are rarely reported. To provide a comprehensive insight into possum neoplasia, a retrospective evaluation of female reproductive disorders of growth in common brushtail possums from the Australian Registry of Wildlife Health (ARWH), Taronga Zoo, and University of Sydney, Veterinary Pathology Diagnostic Services (VPDS), was performed to identify additional cases. Conclusion: The present report describes the first published case report of mammary carcinoma in a common brushtail possum. This article should serve as a valuable reference for the types and relative frequencies of female reproductive disorders of growth that occur in possum species.